Exercise therapy in the application of sleep disorders - Zhao, Yuhang; Dai, Qiang; Li, Yuhao; Li, Chenyang (Frontiers in Neurology, 2024)
Sleep disorders often accompany neurological injuries, significantly impacting patient recovery and quality of life.The efficacy and adherence of traditional treatment methods have certain limitations. Exercise has been found to be a highly beneficial treatment method, capable of preventing and alleviating neurological injuries and sleep disorders. This article reviews relevant research findings from both domestic and international sources over the past few decades, systematically summarizing and analyzing the application of exercise therapy in sleep disorders,strategy of exercise intervention program and the potential molecular mechanisms by which exercise therapy improves sleep disorders. Shortcomings in current research and suggestions are presented, providing a reference for future in-depth studies on exercise interventions for sleep disorders.